Trialing addiction neurocircuitry targets and directionality of brain stimulation effects: A deep TMS/fMRI trial in people with alcohol use disorder - Daniel J. Fehring; Jordan Morrison-Ham; Annalee L. Cobden; Justin Mahlberg; Mengxia Gao; Claire E. Kelly; Arshiya Sangchooli; Devon Stoliker; Emily Giddens; Brody Quinn; Antonia Cholewick; Luiza Bonfim Pacheco; et al. (Contemporary Clinical Trials Communications, 2025)
Background: Excessive alcohol consumption is a global health concern, with an estimated 400 million people living with alcohol use disorder (AUD). Current treatments for AUD have limited efficacy and fail to address its diverse neurobiological underpinnings. There are at least two cortico-striatal circuits relevant to AUD neurobiology: a weakened dorsolateral prefrontal cortex (dlPFC) pathway, and a heightened ventromedial prefrontal cortex (vmPFC) pathway. Purpose: This trial aims to examine whether deep transcranial magnetic stimulation (dTMS) can recalibrate the neurocircuitry disrupted in AUD as a proof-of-concept for its therapeutic potential. We will assess the capacity of two theta-burst stimulation protocols to modify neuroimaging and behavioral indices of AUD-related neurocircuitry alterations. Methods: We will conduct a randomized, single-blind, sham-controlled crossover trial with 30 adults with moderate to severe AUD (aged 18–49). Participants will receive two doses of active or sham dTMS (for 2 sessions; 7 days apart; order counterbalanced) targeting the dlPFC or vmPFC with intermittent or continuous theta-burst stimulation, respectively. Results: Primary, secondary, and exploratory outcomes (i.e., stimulation-induced changes in neural circuit connectivity, executive control/decision-making, and craving-related emotions, respectively) will be collected before and after each dTMS dose. Additional exploratory outcomes (daily craving experiences and weekly alcohol consumption) will be collected across a 90-day period from the first session. Discussion: This trial innovates by utilizing distinct dTMS approaches to specifically target two functionally segregated neurocircuitries disrupted in AUD. Results will inform the development of a larger-scale trial by establishing optimal therapeutic approaches for AUD.